Isolation of high quality DNA: a protocol combining rennet and glass milk - de Oliveira, Luiz Felipe Valter; Wallau, Gabriel da Luz; Silva Loreto, Elgion Lucio (Electronic Journal of Biotechnology, 2009)
High quality DNA is essential for many molecular biology techniques. However, the reagents used for that purpose usually are expensive and/or cause a high environmental impact. Here, we describe two alternative protocols that use inexpensive reagents and are not hazardous to the environment. The first protocol utilizes the enzyme chymosin, normally used as "rennet" in cheese production and which is easily obtained on the commercial market. The second protocol uses "rennet DNA extraction protocol" combined with the DNA binding capacity of glass powder (glass milk), which can easily be "home made". The first protocol is used when a high yield of DNA is needed, whereas the second protocol is used for production of a higher quality DNA, being able to work with sparse samples.